Not a fairy tale at all!: Examining the factors underlying the myths about domestic violence among Romanian, highly educated adults - Gancevici, Olga (Deviant behavior, 2024)
The myths about domestic violence refer to the false, stereotypical beliefs aimed to minimize, deny, or justify the aggression. The present research explored the factors underlying the myths about domestic violence using a socio-cognitive perspective. In a sample of 364 Romanian adults with a university degree, aged 19 to 75 (M = 36.46, SD = 10.97, 79.9% females), we explored how sexism, patriarchal beliefs, moral disengagement, and the Dark Triad traits might predict participants’ views on domestic violence. Regression analyses suggested that, in the male sample, the only predictor for the acceptance of the myths regarding domestic violence was moral disengagement, and the model accounted for more than 50% of the variance of the dependent variable. In the female sample, the strongest predictor was hostile sexism, and the model accounted for more than 40% of the variance of the acceptance of the myths regarding domestic violence. We discuss our results focusing on the practical implications of people’s beliefs about domestic violence and the importance of examining the underlying personal and cultural factors.